ANALISIS KADAR AMONIAK DI UDARA DAN SANITASI PETERNAKAN SERTA KELUHAN KESEHATAN PADA PEKERJA DI PETERNAKAN AYAM DI DESA SEI. LIMBAT KECAMATAN SELESAI KABUPATEN LANGKAT - Dessy Irfi Jayanti; devi nuraini santi; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
Analysis the concentration of ammonia in the air and sanitation of poultry and health sigh on workers in the poultry Desa Sei. Limbat Kecamatan Selesai Kabupaten Langkat. Poultry is the agribusiness that still developed in Indonesia. CV.Bima is poultry located in the stabor Dusun III Desa Sei. Limbat Kecamatan Selesai Kabupaten Langkat. One of the negative impacts of the poultry odor is caused by the high concentration of ammonia gas. This research aims to know The concentration of ammonia in the air and sanitation of poultry and health sigh on workers in the poultry of Desa Sei. Limbat Kecamatan Selesai Kabupaten Langkat. The type of research used is descriptive. Population in this research is 32 people workers that is used in total sampling. The results showed that the concentration of ammonia in the air in poultry of Desa Sei. Limbat Kecamatan Selesai Kabupaten Langkat did not exceeded the level of the quality standard specified in KepMenLH No 50 in 1996. The highest point on range performed in area behind red chicken livestock is 0,1485 ppm. Conclusion of this research is the concentration of ammonia (NH3) in the air have not exceeded the quality standards. Based on the characteristics of workers are age, education, gender, work hours per day, working period, and smoking, there are 9 workers who have respiratory tract disorders and 6 people who have complaints of eye irritation, while for the complaints of skin irritation there are no workers getting it. Therefore it's recommended to chicken farm to be attention health of worker by give self protective tools for workers , execute poultry sanitation properly and taking care of poultry environment. Keywords: poultry, sanitation, health sigh, ammonia